FUNDIC GLAND POLYPS: A HOLYSTIC REVIEW - Baiq Ayu Rahmawati (Jurnal Medika Hutama, 2024)
Gastric polyps are subepithelial protrusions commonly encountered during esophagogastroduodenoscopy (EGD). Fundic gland polyps are the most common type of polyps. The diagnosis of fundic gland polyps can be established through Narrow-band imaging (NBI) and forceps biopsy. Further monitoring is not required for fundic gland polyps that do not have malignant potential. This literature review is conducted using online data sources, namely Sciencedirect, Researchgate, and PubMed. In this literature review, the focus will be on discussing the definition, epidemiology, classification, etiology, risk factors, pathophysiology, clinical manifestations, diagnostic confirmation, management, and differential diagnosis of Fundic gland polyps.